Silicon carbide microsystems for harsh environments - Wijesundara, Muthu B.J.; Wijesundara, Muthu; Azevedo, Robert; SpringerLink (Online service). (New York Springer, 2011)
Silicon Carbide Microsystems for Harsh Environments reviews state-of-the-art Silicon Carbide (SiC) technologies that, when combined, create microsystems capable of surviving in harsh environments. Technological readiness of the system components, key issues when integrating these components into systems, and other hurdles in harsh environment operation are discussed at length. The authors use the SiC technology platform suite as the model platform for developing harsh environment Microsystems, and then detail the current status of the specific individual technologies (electronics, MEMS, packaging). Additionally, methods towards system level integration of components and key challenges are evaluated and discussed based on the current state of SiC materials processing and device technology. Issues such as temperature mismatch, process compatibility and temperature stability of individual components and how these issues manifest when building the system receive thorough investigation. This book also: Addresses the SiC platform for complete microsystems and goes beyond the individual device levelProvides a comprehensive collection of SiC technologies information relevant to harsh environment microsystems. Covers the challenges in combining SiC process and components to a microsystem. Discusses power source and signal transmission issues in the context of the harsh environment application space Silicon Carbide Microsystems for Harsh Environments not only reviews the state-of-the-art MEMS devices, but also provides a framework for the joining of electronics and MEMS along with packaging into usable harsh-environment-ready sensor modules.
Introduction to Harsh MEMs -- Silicon Carbide Processing -- Silicon Carbide Electronics -- Silicon Carbide MEMS Devices -- Silicon Carbide MEMs Device Packaging -- System Integration.
Electronic reproduction.
Keywords: Microelectromechanical systems; Electronic books